Scientific collaboration for early detection of invaders results in a significant update on estimated range: lessons from Stenothoe georgiana Bynum & Fox 1977 - MARTÍNEZ-LAIZ, GEMMA; ROS, MACARENA; GUERRA-GARCÍA, JOSÉ MANUEL; MARCHINI, AGNESE; FERNÁNDEZ-GONZÁLEZ, VICTORIA; VAZQUEZ-LUIS, MAITE; LIONELLO, MONICA; SCRIBANO, GIOVANNI; SCONFIETTI, RENATO; FERRARIO, JASMINE; ULMAN, AYLIN; COSTA, ANA CRISTINA; et al. (Mediterranean Marine Science, 2020)
Detection of new non-indigenous species is often delayed when taxa are taxonomically challenging, such as small-sized marine organisms. The present study highlights the relevance of scientific cooperation in the early detection of the invader amphipod Stenothoe georgiana. Originally described from North Carolina (USA), the species was recently found in Chile and the Western Mediterranean. Here, we provide the first record of the species in Macaronesia, Atlantic coasts of continental Europe, North Africa and Australia, and extend its known distribution along the Mediterranean coast. Just like other small crustaceans, shipping (both ballast water and recreational boating) and aquaculture are probably the main vectors of introduction and secondary spread for this amphipod species. This case of S. georgiana sheds light on the importance of promoting taxonomical knowledge, and building multidisciplinary networks of experts that ensure an effective diessemination of alien species information. We also encourage the implementation of standardized monitoring methodologies to facilitate early detection of small mobile invaders.